Optimum structural modelling for tall buildings - Jameel, M.; Saiful Islam, A.B.M.; Hussain, R.R.; Khaleel, M.; Zaheer, M.M. (2012)
It is a common practice to model multi-storey tall buildings as frame structures where the loads for structural design are supported by beams and columns. Intrinsically, the structural strength provided by the walls and slabs are neglected. As the building height increases, the effect of lateral loads on multi-storey structures increases considerably. The consideration of walls and slabs in addition to the frame structure modelling shall theoretically lead to improved lateral stiffness. Thus, a more economic structural design of multi-storey buildings can be achieved. In this research, modelling and structural analysis of a 61-storey building have been performed to investigate the effect of considering the walls, slabs and wall openings in addition to frame structure modelling. Sophisticated finite element approach has been adopted to configure the models, and various analyses have been performed. Parameters, such as maximum roof displacement and natural frequencies, are chosen to evaluate the structural performance. It has been observed that the consideration of slabs alone with the frame modelling may have negligible improvement on structural performance. However, when the slabs are combined with walls in addition to frame modelling, significant improvement in structural performance can be achieved. Copyright Â© 2012 John Wiley & Sons, Lt